2020
DOI: 10.3389/fgene.2019.01263
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Methylome and Transcriptome Changes Reveals the Underlying Regulatory Signatures Driving Curly Wool Transformation in Chinese Zhongwei Goats

Abstract: The Zhongwei goat is kept primarily for its beautiful white, curly pelt that appears when the kid is approximately 1 month old; however, this representative phenotype often changes to a less curly phenotype during postnatal development in a process that may be mediated by multiple molecular signals. DNA methylation plays important roles in mammalian cellular processes and is essential for the initiation of hair follicle (HF) development. Here, we sought to investigate the effects of genome-wide DNA methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 69 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…We selected two of the 12 candidate DE miRNAs that exhibited extremely significant differences and predicted their target genes. The predicted miRNA target genes were combined with published transcriptomic analysis data from our lab [ 21 ], to construct a mRNA- and miRNA network related to hair bending. Taking the intersection of the results obtained from the two prediction sites, we found that miR-26a has 667 target genes and miR-130a has 184 target genes.…”
Section: Resultsmentioning
confidence: 99%
“…We selected two of the 12 candidate DE miRNAs that exhibited extremely significant differences and predicted their target genes. The predicted miRNA target genes were combined with published transcriptomic analysis data from our lab [ 21 ], to construct a mRNA- and miRNA network related to hair bending. Taking the intersection of the results obtained from the two prediction sites, we found that miR-26a has 667 target genes and miR-130a has 184 target genes.…”
Section: Resultsmentioning
confidence: 99%
“…CEBPB, GATA3, and HOXA5, were under the control of DNA methylation and involved in skin and hair follicle differentiation [28]. Through integrated analysis of the methylome and transcriptome, Xiao found 14 crucial factors for wool fiber development under the control of epigenetic mechanisms during curly fleece dynamics in Zhongwei goats [29]. Li revealed that FMN1, PCOLCE, SPTLC3, and COL5A1 were crucial factors for elucidating the epigenetic mechanisms contributing to the telogen-to-anagen transition in cashmere goats [30].…”
Section: Introductionmentioning
confidence: 99%
“…Promoter methylation of HOTAIR gene and related suppressed expression were found to regulate the reconstruction of secondary hair follicles in cashmere goat ( Jiao et al, 2019 ). Furthermore, crucial regulatory roles for DNA methylation in wool fiber development and transformation of fur with special characters and production purpose, such as curly wool with beautiful white color or high-quality brush hair, have been observed ( Qiang et al, 2018 ; Xiao et al, 2019 ).…”
Section: Evidence Of the Impacts Of Epigenetic Processes On Livestockmentioning
confidence: 99%